EXPRESSION PATTERNS OF AN ABIOTIC STRESS-INDUCIBLE DEHYDRATION RESPONSIVE ELEMENT BINDING PROTEIN-2 (DREB2) GENE IN TOMATO - Islam, M. S.; Wang, M. H. (Bangladesh Journal of Plant Breeding and Genetics, 2012)
<span style="font-size: 10.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Malgun Gothic"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">A novel DREB (dehydration-responsive element<span style="font-size: 10.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Malgun Gothic"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> binding) <span style="font-size: 10.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Malgun Gothic"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">gene, <span style="font-size: 10.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Malgun Gothic"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">designated as <span style="font-size: 10.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Malgun Gothic"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">LeDREB2<span style="font-size: 10.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Malgun Gothic"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">, was isolated from tomato. <span style="font-size: 10.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Malgun Gothic"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Based on multiple sequence alignment and phylogenetic characterization, LeDREB2 gene<span style="font-size: 10.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Malgun Gothic"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> <span style="font-size: 10.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Malgun Gothic"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">was classified into <span style="font-size: 10.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Malgun Gothic"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">an A-2 group member of the DREBs<span style="font-size: 10.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Malgun Gothic"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> family. W<span style="font-size: 10.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Malgun Gothic"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">e examined the expression pattern of LeDREB2 gene <span style="font-size: 10.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Malgun Gothic"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">in tomato under different abiotic stresses. Southern blot analysis <span style="font-size: 10.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Malgun Gothic"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">showed that LeDREB2 <span style="font-size: 10.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Malgun Gothic"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">is a single copy gene in tomato genome.<span style="font-size: 10.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Malgun Gothic"; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;"> <span style="font-size: 10.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Malgun Gothic"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">The organ specific <span style="font-size: 10.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Malgun Gothic"; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;">expression profiling <span style="font-size: 10.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Malgun Gothic"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">indicated<span style="font-size: 10.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Malgun Gothic"; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;"> that <span style="font-size: 10.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Malgun Gothic"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">LeDREB2 gene<span style="font-size: 10.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Malgun Gothic"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> <span style="font-size: 10.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Malgun Gothic"; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;">was <span style="font-size: 10.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Malgun Gothic"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">strongly<span style="font-size: 10.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Malgun Gothic"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> <span style="font-size: 10.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Malgun Gothic"; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;">expressed in <span style="font-size: 10.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Malgun Gothic"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">young <span style="font-size: 10.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Malgun Gothic"; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;">leaves<span style="font-size: 10.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Malgun Gothic"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> and roots but weak expression in mature leaves<span style="font-size: 10.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Malgun Gothic"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> and shoots<span style="font-size: 10.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Malgun Gothic"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">. Northern blot analysis revealed that various <span style="font-size: 10.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Malgun Gothic"; mso-ansi-language: EN-US; mso-fareast-language: KO; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;">kinds of <span style="font-size: 10.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Malgun Gothic"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;">environmental stress<span style="font-size: 10.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Malgun Gothic"; mso-ansi-language: EN-US; mso-fareast-language: KO; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;"> <span style="font-size: 10.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Malgun Gothic"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;">such as salt, drought and cold were <span style="font-size: 10.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Malgun Gothic"; mso-ansi-language: EN-US; mso-fareast-language: KO; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;">significantly <span style="font-size: 10.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Malgun Gothic"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;">induced by <span style="font-size: 10.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Malgun Gothic"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">LeDREB2 gene<span style="font-size: 10.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Malgun Gothic"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> <span style="font-size: 10.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Malgun Gothic"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;">after application of time courses treatments except little increase in ABA. Our findings showed that the expression of LeDREB2 gene was induced by high salinity, drought and cold but not by the abscisic acid (ABA) treatment<span style="font-size: 10.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Malgun Gothic"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;">. <span style="font-size: 10.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Malgun Gothic"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">These results indicated that the LeDREB2 gene is a member of the DREB transcription factors, which may play a role in both abiotic and oxidative stress responses. DOI: http://dx.doi.org/10.3329/bjpbg.v25i1.17006